Bahasa Inggris - Abdillah, Pujangga; Gunawan, Szabyna Regytha Aura; Sarasmitha, Citra; Sihwahjoeni, Sihwahjoeni (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2023)
This study aims to provide a valuable contribution by exploring the moderating effect of audit quality and board gender diversity on the relationship between corporate social responsibility disclosure (CSRD) and corporate tax avoidance (CTA) of Indonesian listed companies. This study used quantitative research by moderated regression analysis (MRA) with the STATA program, and this method used the annual report of firms listed on the Indonesian stock exchange from the 2020-2022 period with a sample of 256 firms. The results showed that CSRD influences CTA as measured by DER. That is, the higher the CSRD made, the more the company can improve CTA. This research shows that audit quality as a moderation variable is proven empirically able to decrease the influence of CSRD on CTA; audit quality has a role in CSR strategy and also shows that BGD as a moderation variable is proven empirically able to increase the influence of CSRD on CTA. Therefore, promoting BGD in corporate decision-making will help the world's leading governments and policymakers achieve Sustainable Development Goals (SDGs).